Ketika Perempuan Tidak Cantik: Analisis Atas Representasi Perempuan dalam Webtoon The Secret of Angel - Mite Setiansah; Vini Fahira Amru (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2021)
Beautiful or not is a socio-cultural construction that is very relative and can be different in every place, time and culture. However, there are beauty standards that are often used as ideal indicators for women to be considered beautiful. When women are deemed not meeting these criteria, then they will be vulnerable to various discriminatory treatment from their environment. As a result, women must always strive to meet these beautiful standards in various ways including using make-up. This condition was revealed in the analysis of the digital comic The Secret of Angel. The analysis was carried out using mix methods approach to 89 comic episodes. The results of the analysis show that quantitatively (66%) of the utterances addressed to women, especially the main character, are positive, but qualitatively when attached to the context, the positive representation does not necessarily have a positive connotation and frees women from discriminatory treatment.